MAKTAB MUSIQA TA’LIMIDA O’QUVCHILARNI DIRIJORLIK AMALIYOTIGA O’RGATISHNING O‘ZIGA XOS XUSUSIYATLARI - Pardayev Sobit Abdivali o‘g‘li; Mirzayev Shaxzod Yunus o‘g‘li (Ustozlar uchun, 2025)
Abstract: Singing in a group (choir) in musical culture lessons in secondary schools is closely related to conducting. In this process, the teacher acts as the leader and conductor of the choir, and at the same time, one of the most important pedagogical tasks is to teach students to sing with an understanding of conducting actions, that is, to acquaint them with basic knowledge of conducting.